Perbandingan Interaksi Karbon Aktif dengan Polaritas Minyak Nabati terhadap Karakteristik Pembakaran Premixed - Purnami, Purnami; Wardana, I Nyoman Gede (Jurnal Rekayasa Mesin, 2021)
Crude oil consumption has increased since the discovery of crude oil-fueled engine technology. However, the increase in crude oil consumption is not offset by the productivity of the product. This results in a reduced availability of crude oil. One solution found was to use alternative fuels from vegetable oils. Several researches have proven that vegetable oils can be used as fuel. The results of the research found potential in jatropha oil and palm oil. However, jatropha oil and palm oil contain glycerol compounds which can affect the results of its combustion, because glycerol can absorb heat and result in firing more difficult. Based on that, modification and development are needed to support the use of jatropha oil and palm oil as alternative fuels by studying oil polarity and adding catalysts for coconut shell-activated carbon. Jatropha oil has low polarity (C18) which is more volatile than palm oil which has high polarity (C13). The variation used in this research is the addition of activated carbon with a concentration of 0 ppm, 200 ppm, and 400 ppm in each oil. The addition of activated carbon will facilitate evaporation because oil molecules become more reactive more freely.